Community Empowerment For Rural Tourism Development In Golden Village, Gunungkidul - Tristanti Tristanti; Fitta Ummaya Santi; Fitriana Tjiptasari; Sujarwo Sujarwo (LPPM Universitas PGRI Sumatera Barat, 2025)
Development tourist No regardless of role public as key its implementation. By because it is empowerment public become important done so that objective tourist can achieved. The aim of this research is to : 1) describe process empowerment public in development tourist rural areas in the village gold ; 2) describe weakness process empowerment public in development tourist rural areas in the village gold ; 3) Formulate model conceptual empowerment public in development tourist rural areas in the village gold. Approach this research is qualitative with type studies case.. Data collection techniques using observation, documentation, interviews and FGD ( Focus Group Discussion ). The data analysis technique used stages data collection, data condensation, data presentation and withdrawal Conclusion. The results of this study are : 1) The process empowerment public in development tourist rural areas in the village gold covering awareness, capacity building, implementation and monitoring, evaluation and sustainability ; 2) weaknesses process empowerment public in development tourist the village in Kampung Emas, namely limited ability source Power human, partner limitations, and not yet There is intensive assistance from the government area ; 3) composition model conceptual empowerment public in development tourist countryside in Kampung Emas